a9_soln

# a9_soln - Math 237 Assignment 9 Solutions 1 Consider the...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 237 Assignment 9 Solutions 1. Consider the following maps T : R 2 → R 2 . Find the image under T of the rectangle D = { ( x,y ) ∈ R 2 | ≤ x ≤ 2 ,- 2 ≤ y ≤ 2 } . a) T ( x,y ) = ( x cos( πy/ 3) ,x sin( πy/ 3)) . Solution: We have u = x cos( πy/ 3) and v = x sin( πy/ 3) . For x = 0 ,- 2 ≤ y ≤ 2 we have ( u,v ) = T (0 ,y ) = (0 , 0) . So, the image of the line is the point (0 , 0) . For the line x = 2 ,- 2 ≤ y ≤ 2 we have ( u,v ) = T (2 ,y ) = (2 cos( πy/ 3) , 2 sin( πy/ 3)) ,- 2 ≤ y ≤ 2 . We recognize this as a parametric equation for an arc of a circle of radius 2 from angle- 2 3 π to 2 3 π . Thus, the image is the arc of the circle u 2 + v 2 = 4 over these angles. For the line y =- 2 , ≤ x ≤ 2 we have ( u,v ) = F ( x,- 2) = (- 1 2 x,- √ 3 2 x ) . Hence, we have v =- √ 3 2 x = √ 3 u . Moreover, since ≤ x ≤ 2 , then- 1 ≤ - 1 2 x ≤ so- 1 ≤ u ≤ . Hence, the image is the line v = √ 3 u , for- 1 ≤ u ≤ . For the line y = 2 , ≤ x ≤ 2 we have ( u,v ) = F ( x, 2) = (- 1 2 x, √ 3 2 x ) . Hence, we have v = √ 3 2 x =- √ 3 u . Moreover, since ≤ x ≤ 2 , then- 1 ≤ - 1 2 x ≤ so- 1 ≤ u ≤ . Hence, the image is the line v =- √ 3 u , for- 1 ≤ u ≤ . b) T ( x,y ) = ( x 2- y 2 ,xy ) . Solution: We have u = x 2- y 2 and v = xy . For x = 0 ,- 2 ≤ y ≤ 2 we have ( u,v ) = T (0 ,y ) = (- y 2 , 0) . Thus, we have v = 0 and since- 2 ≤ y ≤ 2 and u =- y 2 , we get that u runs from- 4 to and then from to- 4 . For x = 2 ,- 2 ≤ y ≤ 2 we have ( u,v ) = T (2 ,y ) = (4- y 2 , 2 y ) . Thus, we have v 2 = y and so u = 4- y 2 = 4- v 2 4 . Since- 2 ≤ y ≤ 2 , we get- 2 ≤ v 2 ≤ 2 ⇒ - 4 ≤ v ≤ 4 . 2 For y = 2 , ≤ x ≤ 2 we have ( u,v ) = T ( x, 2) = ( x 2- 4 , 2 x ) . Thus, we have v 2 = x and so u = x 2- 4 = v 2 4- 4 . Since ≤ x ≤ 2 , we get ≤ v 2 ≤ 2 ⇒ ≤ v ≤ 4 . For y =- 2 , ≤ x ≤ 2 we have ( u,v ) = T ( x,- 2) = ( x 2- 4 ,- 2 x ) . Thus, we have- v 2 = x and so u = x 2- 4 = v 2 4- 4 . Since ≤ x ≤ 2 , we get ≤ - v 2 ≤ 2 ⇒ - 4 ≤ v ≤ ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 8

a9_soln - Math 237 Assignment 9 Solutions 1 Consider the...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online